Dyadic, Partner, and Social Network Influences on Intimate Partner Violence among Male-Male Couples - Rob Stephenson (Western Journal of Emergency Medicine, 2013)
Introduction: Despite a recent focus on intimate partner violence (IPV) among men who have sex with men (MSM), the male-male couple is largely absent from the IPV literature. Specifically, research on dyadic factors shaping IPV in male-male couples is lacking.Methods: We took a subsample of 403 gay/bisexual men with main partners from a 2011 survey of approximately 1,000 gay and bisexual men from Atlanta. Logistic regression models of recent (,12 month) experience and perpetration of physical and sexual IPV examined dyadic factors, including racial differences, age differences, and social network characteristics of couples as key covariates shaping the reporting of IPV.Results: Findings indicate that men were more likely to report perpetration of physical violence if they were a different race to their main partner, whereas main partner age was associated with decreased reporting of physical violence. Having social networks that contained more gay friends was associated with significant reductions in the reporting of IPV, whereas having social networks comprised of sex partners or closeted gay friends was associated with increased reporting of IPV victimization and perpetration.Conclusion: The results point to several unique factors shaping the reporting of IPV within male-male couples and highlight the need for intervention efforts and prevention programs that focus on male couples, a group largely absent from both research and prevention efforts. [West J Emerg Med. 2013;14(4):316–323.]